Scurvy: An unusual presentation of cerebral palsy - Gupta, Sumit (Baishideng Publishing Group Co., Limited, 2012)
Scurvy is caused by prolonged severe dietary deficiency of ascorbic acid, in which the breakdown of intercellular cement substances leads to capillary hemorrhages and defective growth of fibroblasts, osteoblasts and odontoblasts, resulting in impaired synthesis of collagen, osteoid and dentine. It is characterized by hemorrhagic gingivitis, subperiosteal hemorrhages, perifollicular hemorrhages, and frequently petechial hemorrhages (especially on the feet). People with abnormal dietary habits, mental illness or physical disability are prone to develop this disease. Epiphyseal separation is known to occur in scurvy but is rarely seen now. Epiphyseal separation from the metaphysis is always through the zone of calcified cartilage, known as “scorbutic lattice”, which in the radiographs is represented as “the white line of Frenkel”. We report a case of multiple epiphyseal separations in a cerebral palsy child because of vitamin C deficiency. The child was treated with splintage of extremity and nutritional supplementation. All physeal separation healed completely without any deformity.